Competence management models in leading Brazilian organizations - Fernandes, Bruno Henrique Rocha; Bitencourt, Claudia Cristina; Comini, Graziella Maria (Revista de Administração da UFSM, 2021)
Purpose: To investigate into the strategic alignment of competency-based management (CBM) models implemented in 95 Brazilian organizations, leaders in their respective segments. Design / methodology / approach: The study is a longitudinal, exploratory-descriptive study under a qualitative and quantitative approach. Findings: A great similarity was found in the competencies in the CBM models, both in terms of incidence of competencies and similarity of their descriptions. Research limitations / implications: The study reveals a trend towards a disconnection between individual competencies and organizational strategies and values, and suggests four possible propositions to be investigated in future studies: P1: Absence of conceptual rigor for competences; P2: Insufficient dedication of time to implement a model; P3: Dissemination of “off-the-shelf models”, and P4: Institutionalization of CBMs as a dominant practice for people management. Practical implications: The results point to the need for organizations, when building or updating their CBM models, to pay attention to the concept of competencies used, ensuring the incorporation of the organizational strategy into the model, and dedicating adequate time to its elaboration and implementation in order to customize the CBM model to their needs. Originality / value: It constitutes one of the few longitudinal surveys with a representative sample of existing CBM models in Brazil and worldwide; hence, it captured a phenomenon (homogenization of CBM) that has been difficult to be observed outside this research.